The Relationship between the Organic Material Content of Sediments and the Abundance of Macrozoobentos in Saruang Sakin Beach, Sungai Nyalo Village, West Sumatra Province - Afdol, Muhammad; Nedi, Syahril; Tanjung, Afrizal (Journal of Coastal and Ocean Sciences, 2023)
This research was conducted in June 2022 in the coastal area of ​​Saruang Sakin, Sungai Nyalo Village, West Sumatra Province. This study examines the relationship between sediment organic matter content and the abundance of macrozoobenthos. The method used in this study is the survey method, in which samples will be taken directly at the research location, sediment sampling using a pipe with a size of 10 cm and a length of 70 cm, and macrozoobenthos samples taken directly by hand and a shovel in a plot with a size each plot 1 m x1 m, to see the relationship between the organic matter content of the sediment and its abundance, a simple linear regression test was carried out. Sediment samples were analyzed in the marine chemistry laboratory, and macrozoobenthos samples were analyzed in the marine biology laboratory. This study's results indicate that the sediment's organic matter content ranges from 1.03% - 4.30%. The abundance of macrozoobenthos between study stations obtained an average abundance value of 3.44-5.89 ind/m². The simple linear regression test results obtained a correlation value of 0.092 with a coefficient of determination of 0.1 and a significance value of 0.942